Uncommon complication after off-pump coronary artery bypass grafting procedure in case of Patient with end stage heart failure - Woźniak, Sebastian; Kuśmierczyk, Mariusz; Kołsut, Piotr; Kuśmierski, Krzysztof; Różański, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
A case of 79-year-old man with coronary artery disease and hart failure. We performe OPCAB Procedure. Complications after procedure, local , and systemic bacterial infection couse left eye enucleation on 25 postoperative day.